Effects of thought content instructions on swimming performanc - Rushall, B. S.; Shewchuk, M. L. (The Journal of Sports Medicine and Physical Fitness, 1989)
Six superior Canadian age-group swimmers were instructed in positive thinking. Personal thoughts were planned and practiced for a brief time then used in two different training sets. Ss were instructed to use the positive thinking they had planned on one trial and then alternate it with the normal thinking they usually used at practice. Two 400 m effort swims were completed. Each was divided into 100 m segments and the two types of thoughts were alternated in each trial for each segment. The order of alternation was reversed for the second trial. Four Ss improved, one did not change, and one went fractionally worse for an average time improvement of -1.39% for positive thinking segments. The second task comprised eight 100 m repetitions at steady pace. Each repetition was alternated between a positive thinking trial and a normal thinking trial. All Ss improved their times by an average of -2.13% over normal thinking when using positive thinking. Despite the nature of the training task, positive thinking significantly increased the performance standard of these age-group swimmers. The type of task may influence the magnitude and nature of the positive thinking response for a minor number of swimmers. Implication: Young serious swimmers can improve their training performances by concentrating on planned positive thoughts. The procedure to develop positive thoughts is not time-consuming nor demanding and appears to be a viable activity for improving the quality of training responses. It is reasonable to expect similar improvements with young people in other sports.